Benzoquinone-Promoted Aerobic Oxidative Hydroxylation of Arylboronic Acids in Water - Cheng, Guolin; Zeng, Xiaobao; Cui, Xiuling (Synthesis, 2014)
A general and efficient aerobic oxidative hydroxylation of arylboronic acids promoted by benzoquinone in water was realized, and provided phenols in 72–95% yields for 20 examples. The main advantages of this protocol are the use of water as solvent in the presence of a catalytic amount of benzoquinone, and metal-free conditions.
Keywords: benzoquinone; arylboronic acids; oxidation; oxygen; phenols